The reducing phubbing behavior among high school students: Application of live modeling technique - Masrukhin, Akhmad Rudi; Muslihati, Muslihati; Permana, Veri Susanto Yoga (Universitas Ahmad Dahlan, 2023)
The phenomenon of phubbing, which is increasingly widespread, especially among students, is caused by excessive use of social media on smartphones. However, serious handling is needed to reduce such addictive behavior. This study aims to determine the effectiveness of the level of classical guidance with live modeling techniques related to communication disorders and smartphone obsession of students in State Senior High School 1 Kencong Jember Indonesia. Using a quantitative approach and field research type with one group pretest-posttest design experiment method, the sample was determined purposively with 35 students out of 1116 populations. The instrument used in this research is a phubbing scale which has been tested for validity and reliability. Data analysis used paired sample t-test. The research results showed that there were differences in students' phubbing levels before and after being given classical guidance treatment using live modeling techniques. Aspects of phubbing which include communication disturbance and smartphone dependency, both decreased significantly after being given treatment in the form of classical guidance on live modeling techniques. Counselors can use live modeling as an alternative guidance technique to reduce phubbing.